2008
DOI: 10.1021/nn700151z
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Highly Water-Soluble Fullerenes More Than Half-Covered by Hydroxyl Groups

Abstract: Using a novel hydrogen peroxide heating method, we synthesized milky white, water-soluble polyhydroxylated fullerenes (fullerenols) with 36-40 hydroxyl groups (estimated average) along with 8-9 secondary bound water molecules. The fullerenols exhibited high water solubility up to 58.9 mg/mL in a neutral (pH = 7) condition. Dynamic light scattering analysis showed a high dispersion property, to give a narrow particle size distribution within 0.7-2.0 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
193
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(216 citation statements)
references
References 44 publications
19
193
2
Order By: Relevance
“…The research work related to fullerenols embraces wide spectrum of areas, e.g., studies of their electrolytic properties, 11 physicochemical characterization of their properties in water 12 and use in catalytic processes, 13 studies related to their application in drug delivery 14 and their biological activity. 15 Due to the popularity of fullerenols there still exists a need for improving the synthesis 16 and analytical methods for establishing their characterization. 17 During our recent attempts to further optimize hydrolysis of ethyl ester of T h -FHMA we have observed that under certain conditions a nucleophilic addition of -OH groups to fullerene C 60 cage takes place as a side reaction, leading to the formation of some kind of a hybrid with features of T h -symmetric FHMA and fullerenol (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The research work related to fullerenols embraces wide spectrum of areas, e.g., studies of their electrolytic properties, 11 physicochemical characterization of their properties in water 12 and use in catalytic processes, 13 studies related to their application in drug delivery 14 and their biological activity. 15 Due to the popularity of fullerenols there still exists a need for improving the synthesis 16 and analytical methods for establishing their characterization. 17 During our recent attempts to further optimize hydrolysis of ethyl ester of T h -FHMA we have observed that under certain conditions a nucleophilic addition of -OH groups to fullerene C 60 cage takes place as a side reaction, leading to the formation of some kind of a hybrid with features of T h -symmetric FHMA and fullerenol (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The narrow particle-size distributions around 1-2 nm in terms of the number of C 60 (OH) 36 and C 60 (OH) 44 molecules are essentially the same, indicating the highly dispersed nature of the fullerenols at a molecular level (Figure 3) (Kokubo et al, 2008;Kokubo et al, 2011). The average particle size of C 60 (OH) 44 was determined to be 1.46 ± 0.38 nm (N = 8).…”
Section: Dynamic Light Scattering Methodsmentioning
confidence: 85%
“…Thus, we have found a new and facile approach for synthesizing high-degree fullerenols that have high water solubility without using any Na salts (Kokubo et al, 2008). The reddish brown suspension of fullerenol C 60 (OH) 12 in 30% aqueous H 2 O 2 was stirred vigorously at 60 °C under air until it turned to a transparent yellow solution, which occurred within 2-4 days (Scheme 2a).…”
Section: Highly Polyhydroxylated Fullerenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the latter, while pristine C60 is not water soluble, functionalization with polar groups leads to derivatives with higher water affinity (Wang et al, 2005;Kokubo et al, 2008), which in some cases promotes the formation of hydrates from water solutions (Zachariah et al, 2015).…”
mentioning
confidence: 99%